2016
DOI: 10.1002/14651858.cd011392.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Management strategies for pancreatic pseudocysts

Abstract: Very low-quality evidence suggested that the differences in mortality and serious adverse events between treatments were imprecise. Low-quality evidence suggested that short-term HRQoL (four weeks to three months) was worse, and the costs were higher in the open surgical drainage group than in the EUS-guided drainage group. Low-quality or very low-quality evidence suggested that EUS-guided drainage with nasocystic drainage led to fewer adverse events than EUS-guided or endoscopic drainage, and shorter hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
1
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 32 publications
0
28
1
4
Order By: Relevance
“…A Cochrane review has looked at the different treatment options for pancreatic pseudocysts [15]. Percutaneous drainage, endoscopic and endoscopic ultrasound drainage and open surgical management have all been described [15,16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Cochrane review has looked at the different treatment options for pancreatic pseudocysts [15]. Percutaneous drainage, endoscopic and endoscopic ultrasound drainage and open surgical management have all been described [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…A Cochrane review has looked at the different treatment options for pancreatic pseudocysts [15]. Percutaneous drainage, endoscopic and endoscopic ultrasound drainage and open surgical management have all been described [15,16]. These procedures are not without serious adverse events but the highest was seen in open surgical drainage (15%)-however, the review did not reach statistical significance [15].…”
Section: Discussionmentioning
confidence: 99%
“…3,4 The drainage of this lesions is indicated when the symptoms persist more than 6 weeks, when the cyst is larger than 6cm in diameter, is rapidly enlarging or some complication is present. 4,5 The options for drainage include endoscopic function, open surgical drainage with cystogastrostomy, cystoduodenostomy and Rouxen-Y cystojejunostomy, or these techniques with minimally invasive approach by laparoscopy. The endoscopic drainage is indicated when there is an immature cyst or is infected, is the less invasive but the recurrence is as high as 30%.…”
Section: Discussionmentioning
confidence: 99%
“…One randomized controlled trial involving 40 subjects demonstrated endoscopic therapy has similar efficacy to surgical drainage and was associated with improved quality of life and decreased healthcare utilization [36]. A recent meta-analysis showed similar results favoring an endoscopic approach; however, these findings were based on low quality evidence and should be interpreted cautiously [37]. …”
Section: Miscellaneous Complications Of Cpmentioning
confidence: 99%